Investigation of COVID-19 outbreak as a case study in Italy using different fractional operators (Journal of Mathematical Modeling and Fractional Calculus, 2024)
This work analyzes the COVID-19 fractional order SEIQRD compartmental model using the six primary categories of the Caputo approach. Numerous conclusions have been drawn on the the solution’s boundedness and non-negativity, as well as the existence and uniqueness of the new mod el. Our findings reveal that the When R0 < 1, the system is locally asymptotically stable at infection-free equilibrium. We also observed that In the absence of illness, the system is globally asymptotically stable (R of Covid 19
Keywords: Mathematical modeling; Boundedness; Existence; Stability analysis